Foraminíferos bentónicos del Cenozoico del pozo Estrella x-l, Cuenca del Colorado, plataforma continental argentina - Carames, Andrea Alejandra (2000)
In the Estrella x-I a sedimentary succession between 540-1,890 meters below surface, comprises strata of Paleocene-Pleistocene age, where 169 taxa were identified. Seven sections may be recognized, each one equivalent to formal stratigraphic units known in the area. The first (540 mbs) bears the Buccella peruoiana f. campsi assemblage of Pleistocene age. The second (630?-990 mbs) has the Cassidulina spp. assemblage of late Middle Miocene to Pliocene age. The third (1,080-1,170 mbs) bears an arenaceous assemblage of probable Middle Miocene age. The fourth (1,260-1,620 mbs) has the Uvigerina spp. assemblage of Early Miocene age. The fifth (1,710 mbs) has abundant glauconite, scarce forarninifera, and is Early Oligocene in age. The sixth (1,800 mbs) has glauconite, poorly preserved forarninifera, scarce radiolarians, and is Middle Eocene to Early Oligocene in age. Finally, the seventh (1,890 mbs) has Buliminella isabelleana f. procera of Paleocene age. A paleoecological interpretation for each section is proposed.